A COMPARATIVE STUDY ON RISK OF OSTEOPOROSIS ASSOCIATED WITH THE USE OF VALPROATE VERSUS LEVETIRACETAM IN EPILEPTIC PATIENTS AND ITS RELATIONSHIP WITH METHYLENE TETRA-HYDRO FOLATE REDUCTASE GENOTYPES - FAREEDULLAH, MOHAMMED; RAFI, REHAB; NAAZ, NEHA; ALI SHAMS, MOHAMMED BARKATH; SHAISTA BABAR, SYEDA; ISHAQ, MOHAMMED; MOHIUDDIN JALAAL, MOHAMMED; JAWALKAR, SRIKANTH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study objects at assessing and comparing the intensity of the effect of valproate (VPA) and levetiracetam (LV) on the bone mass in young adult epileptic patients while distinguishing their methylene tetra-hydro folate reductase (MTHFR) genotypes and correlating MTHFR polymorphism and antiepileptic drugs (AEDs) usage with the risk of development of osteoporosis. Methods: The study design was a comparative, prospective, and observational study. It was conducted at Princess Esra Hospital (PEH), Hyderabad and genotype testing was carried out at Salar-e-Millat Research lab (PEH). The consent was obtained from total 70 subjects, divided into three groups: Group 1: 18 patients receiving sodium VPA monotherapy Group 2: 17 patients receiving LV monotherapy Group 3: 35 healthy control subjects from general population. Patients of either gender within age group of 15–40 years, experiencing generalized tonic-clonic seizures or focal seizures, receiving the AED for duration of time ≥2 years were included in the study. Results: Our study showed significant correlation between the AEDs treatment and MTHFR polymorphism in predisposing osteoporosis. Conclusion: The variants of MTHFR gene (C677T) are prone to develop increased levels of homocysteine as a result of decreased activity of the enzyme in their bodies which are further increased in patients receiving AEDs. Monitoring of homocysteine levels in epileptic patients especially in the mutants of MTHFR gene along with their periodic testing of bone mineral density levels is recommended. Treatment for low folate and calcium levels is recommended in these patients to correct their deficiencies.